Unraveling fishers' perceptions: Impact of mining on fish yield and diversity in Mwenga, South Kivu, Eastern Democratic Republic of Congo - Dieudonné Shukuru Wasso; Daud Kassam; Adolphe Kwakanaba Mweze; Socrate Kamani Tungidi; Emmanuel Tulinabo Ahanyirwe; Christian Masumbuko Baraka; Rodrigue Balthazar Basengere Ayagirwe (Ecotoxicology and Environmental Safety)
In South Kivu province, Eastern Democratic Republic of Congo, a significant number of active mines are situated near strictly protected ecosystems, where adverse effects including deforestation, water pollution, soil degradation and loss of biodiversity have been documented. Understanding the local communities' perceptions of how mining affects fish diversity and yield is crucial for fostering a harmonious relationship among stakeholders and preserving the environment and its biodiversity, particularly in Mwenga territory where mining activities are widespread. This study aimed to establish the typology of fishers, and to investigate their perceptions and drivers of these perceptions regarding the impact of mining operations on fish yield and diversity in the Mwenga territory, Democratic Republic of Congo. A cross-sectional survey involving 75 randomly selected fishers was conducted, and data were collected through structured questionnaires. Water quality parameters were measured at three different monitoring sites along the Zalya-Elila River, a primary watercourse in the Mwenga territory. Principal component analysis identified two distinct groups of fishers. Key factors influencing the diversity of Mwenga fishers included age, household size, monthly income, fishing experience, number of fish caught daily 15 years ago, distance between the river and the mine site, fishing hours per day, weekly fishing frequency, and quantity (weight) of fish caught per day currently and 15 years ago (p < 0.05). A significant proportion (39.02 %) of surveyed fishers reported a decline in fish diversity due to mining activities, with only seven out of the 13 previously present fish species remaining in the study area. Moreover, the average catch per fisher per day decreased from 9.00 ± 4.20 Kg 15 years ago to 4.45 ± 1.88 Kg currently. Various factors influenced fishers' perceptions, including age, marital status, education level, household size, comparison of current and past fish catches, presence of nearby mining sites, fishing hours per day, pollution, interconnections between water bodies, and the sediment presence in water bodies (p < 0.05). Among the 11 water parameters monitored, only the temperature, dissolved oxygen, biological oxygen demand over five days, chlorite concentration, sulfate, and nitrate met acceptable and desirable ranges for fish in natural ecosystems. The information obtained from this study constitutes a prerequisite for developing and implementing studies or policies aimed at mitigating and combatting the negative effects of mining on fish yield and diversity in the Mwenga territory. Actions and policies are needed from local authorities to ensure the sustainability of fish biodiversity in the Mwenga territory.